2023
DOI: 10.1093/nsr/nwad048
|View full text |Cite
|
Sign up to set email alerts
|

Bio-robotics research for non-invasive myoelectric neural interfaces for upper-limb prosthetic control: a 10-year perspective review

Abstract: A decade ago, a group of researchers from academia and industry identified a dichotomy between the industrial and academic state-of-the-art in upper-limb prosthesis control, a widely used bio-robotics application. They proposed four key technical challenges, if addressed, could bridge this gap and translate academic research into clinically and commercially viable products. These challenges are unintuitive control schemes, lack of sensory feedback, poor robustness, and single sensor modality. Here, we provide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 131 publications
0
7
0
Order By: Relevance
“…The development of nonclassical robotic systems has been boosted by the increase in application areas where the use of rigid robotic structures is not feasible [ 1 ]. There exist several problems of this kind, such as endoscopic applications, the manipulation of objects in restricted spaces, the implementation of prosthesis devices, the exploration of closed spaces, and so on [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The development of nonclassical robotic systems has been boosted by the increase in application areas where the use of rigid robotic structures is not feasible [ 1 ]. There exist several problems of this kind, such as endoscopic applications, the manipulation of objects in restricted spaces, the implementation of prosthesis devices, the exploration of closed spaces, and so on [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the practical applications of prosthetic hands are hindered due to lacking of a robust humanmachine interface with intuitive and flexible control systems [3]. In the past decades, surface electromyogram (sEMG) played an essential role in establishing control interfaces because of its convenience and non-invasiveness [4]. The sEMG signals are regarded as the summation of motor unit action potentials (MUAPs) containing the neural control information from the central nervous system (CNS) [5].…”
Section: Introductionmentioning
confidence: 99%
“…However, these methods require a large training set that includes all possible task patterns [9]- [12]. Consequently, the training phase becomes extensive and cumbersome, posing a significant hurdle to the practical application of prosthetics [4], [13]. This arduous and time-consuming training process significantly increases user's burden.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, deep learning methods have gained increased attention and become an effective tool for processing and decoding sEMG signals for gesture recognition [13], [14] [16]. To reduce the number of parameters and training data, Tsinganos et al proposed a temporal convolutional network structure and showed higher classification accuracy than that of CNN on a public sEMG dataset [17].…”
Section: Introductionmentioning
confidence: 99%
“…They were all representative structures over the development of deep learning and employed for forearm sEMG-based gesture recognition in previous studies [21]. CNN was widely used in biosignal processing for extracting spatial information [14]. GRU, TCN, and Transformer were all proposed in the last decade, introducing different mechanisms to improve the accuracy and efficiency of sequential data [21].…”
Section: Introductionmentioning
confidence: 99%